Construction of the small intestine on molecular dynamics simulation and preliminary exploration of drug intestinal absorption prediction. (August 2022) - Shi, Yanshuang; Sheng, Mengke; Zhou, Qing; Liao, Yuyao; Lv, Lijing; Yang, Jiaqi; Peng, Xinhui; Cen, Shuai; Dai, XingXing; Shi, Xinyuan
Abstract: In this study, molecular dynamics simulation was applied to the construction of the small intestinal epithelial cell membrane and prediction of drug absorption. First, we constructed a system of a small intestinal epithelial cell membrane that was close to the real proportion and investigated the effects of temperature, water layer thickness, and ionic strength on membrane properties to optimize environmental parameters. Next, three drugs with different absorptivity, including Ephedrine (EPH), Quercetin (QUE), and Baicalin (BAI), were selected as model drugs to study the ability of drugs through the membrane by the free diffusion and umbrella sampling simulation, and the drug permeation ability was characterized by the free diffusion coefficient D and free energy barrier (△G) in the processes. The results showed that the free diffusion coefficient D and △G orders of the three drugs were consistent with the classical experimental absorption order, indicating that these two parameters could be used to jointly characterize the membrane permeability of the drugs. Graphical Abstract: ga1 Highlights: A model of the small intestinal epithelial cells close to the the real proportion was bulit based on the CHARMM-GUI platform. Parameters of model optimization: the temperature was 310 K, water layer thickness was 22.5 Å, ionic strength was 0.15 mol. The diffusion coefficient D and △G of the model drugs can be used to jointly characterize the absorption rate of the drugs.